2023
DOI: 10.3389/fonc.2023.1176038
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and PPAR-gamma in the limelight of brain tumors and edema

Eduard Yakubov,
Sebastian Schmid,
Alexander Hammer
et al.

Abstract: Human malignant brain tumors such as gliomas are devastating due to the induction of cerebral edema and neurodegeneration. A major contributor to glioma-induced neurodegeneration has been identified as glutamate. Glutamate promotes cell growth and proliferation in variety of tumor types. Intriguently, glutamate is also an excitatory neurotransmitter and evokes neuronal cell death at high concentrations. Even though glutamate signaling at the receptor and its downstream effectors has been extensively investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 122 publications
0
1
0
Order By: Relevance
“…This dual regulatory function of p53 holds great potential for cancer treatment (Kang et al, 2019). Additionally, ROS accumulation induces endoplasmic reticulum stress, affecting the activity of peroxisome proliferator-activated receptor (PPAR) (Yakubov et al, 2023) and influencing iron metabolism through inflammatory signaling pathways (Cheng et al, 2021a;Zhao et al, 2023). Moreover, as research progresses, emerging potential targets and receptors are being identified.…”
Section: Ferroptosis Induced By Other Pathwaysmentioning
confidence: 99%
“…This dual regulatory function of p53 holds great potential for cancer treatment (Kang et al, 2019). Additionally, ROS accumulation induces endoplasmic reticulum stress, affecting the activity of peroxisome proliferator-activated receptor (PPAR) (Yakubov et al, 2023) and influencing iron metabolism through inflammatory signaling pathways (Cheng et al, 2021a;Zhao et al, 2023). Moreover, as research progresses, emerging potential targets and receptors are being identified.…”
Section: Ferroptosis Induced By Other Pathwaysmentioning
confidence: 99%